The Psychological Well-Being of Newly-Arrived Indonesian Students in Taiwan - Rahman, Ferry Fadzlul; Lin, Kuan_Han; Hamka, (Journal of International Students, 2020)
A study abroad program is of great interest among high school leavers globally. Indonesian school leavers are no exception. This study investigates the psychological well-being of Indonesian students studying at Taiwanese universities. Informed by a phenomenological approach, sixteen Indonesian participants who studied in Taiwan were recruited for this case study. Data were garnered from semi-structured interviews and observations. The findings of the study show that the students were unable to manage their emotions (e.g., culture shock, a feeling of being isolated) and adapt with different cultures and languages.